Assessing Colonic Exposure, Safety, and Clinical Activity of SRT2104, a Novel Oral SIRT1 Activator, in Patients with Mild to Moderate Ulcerative Colitis. Issue 3 (March 2016) - Sands, Bruce E.; Joshi, Shashidhar; Haddad, Jonathan; Freudenberg, Johannes M.; Oommen, Deepa Elizabeth; Hoffmann, Ethan; McCallum, Stewart W.; Jacobson, Eric
Abstract : Background: Sirtuins are a class of proteins with important physiologic roles in metabolism and inflammation. Sirtuin (silent mating type information regulation 2 homolog) 1, or SIRT1, activation is an unexplored therapeutic approach for the treatment of ulcerative colitis (UC). Methods: Patients with mild to moderately active UC were blindly randomized to 50 mg or 500 mg daily of SRT2104, a selective activator of SIRT1, for 8 weeks. Colonic exposure and safety were assessed, as well as blinded endoscopic scoring and disease activity by Mayo score, Simple Clinical Colitis Activity Index and fecal calprotectin. Results: Across both SRT2104 groups, only 3 of 26 evaluable subjects achieved remission on blinded endoscopic assessment. Clinical remission (Mayo score ⩽2, no subscore >1) was achieved in 4 patients (2 of 13 evaluable patients in each dose group). Fecal calprotectin levels declined with treatment in both groups, but after 56 days of treatment subjects were still found to have levels approximately 4-fold elevated above normal. One subject experienced an SAE requiring study withdrawal and another was withdrawn for a severe UC flare; 19 subjects (61%) across both treatment groups experienced at least 1 treatment emergent adverse event. Average drug exposure increased in a dose-dependent manner for escalating doses of SRT2104, and colonic exposure was 140 to 160 times higher than plasma exposures. Conclusions: SRT2104 did not demonstrate significant clinical activity in mild to moderately active UC. This suggests that further evaluation of SRT2104 as a therapeutic strategy for the treatment of UC is not warranted. Abstract : Article first published online 23 November 2015.